2003
DOI: 10.1645/0022-3395(2003)089[0062:rpamob]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Phagocytosis and Melanization of Bacteria and Plasmodium Sporozoites by Hemocytes of the Mosquito Aedes Aegypti

Abstract: Mosquitoes are vectors of many deadly and debilitating pathogens. In the current study, we used light and electron microscopies to study the immune response of Aedes aegypti hemocytes to bacterial inoculations, Plasmodium gallinaceum natural infections, and latex bead injections. After challenge, mosquitoes mounted strong phagocytic and melanization responses. Granulocytes phagocytosed bacteria singly or pooled them inside large membrane-delimited vesicles. Phagocytosis of bacteria, Plasmodium sporozoites, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
172
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(190 citation statements)
references
References 33 publications
14
172
1
Order By: Relevance
“…In addition to their role in housekeeping protein synthesis, insects use large amounts of aromatic substrates during ecdysis (Sugumaran, 2000), cuticle hardening and tanning (Sugumaran and Nelson, 1998;Vincent, 2002), egg chorion formation (Li, 1994); wound healing (Galko and Krasnow, 2004;Shi et al, 2006), immunity (Siva-Jothy andThompson, 2002), melanotic encapsulation of pathogens (Hillyer et al, 2003;Koella and Sorensen, 2002), neurotransmission (Caveney and Donly, 2002;Osborne, 1996) and hormonal signaling (Gade and Goldsworthy, 2003;Kelly et al, 1994). Hence the demand for aromatic substrates is expected to be accompanied by an elevated expression of aromatic NATs.…”
Section: Role Of the Agnat6-agnat8 Duet In Secretory Epitheliamentioning
confidence: 99%
“…In addition to their role in housekeeping protein synthesis, insects use large amounts of aromatic substrates during ecdysis (Sugumaran, 2000), cuticle hardening and tanning (Sugumaran and Nelson, 1998;Vincent, 2002), egg chorion formation (Li, 1994); wound healing (Galko and Krasnow, 2004;Shi et al, 2006), immunity (Siva-Jothy andThompson, 2002), melanotic encapsulation of pathogens (Hillyer et al, 2003;Koella and Sorensen, 2002), neurotransmission (Caveney and Donly, 2002;Osborne, 1996) and hormonal signaling (Gade and Goldsworthy, 2003;Kelly et al, 1994). Hence the demand for aromatic substrates is expected to be accompanied by an elevated expression of aromatic NATs.…”
Section: Role Of the Agnat6-agnat8 Duet In Secretory Epitheliamentioning
confidence: 99%
“…But because mosquito hemocytes are difficult to collect from mosquitoes and cannot be cultured or even maintained for significant amounts of time in vitro, they have received little research attention. Hemocytes phagocytose and melanize large numbers of bacteria, fungi, and malaria parasites (15,24,25,28,29). Several subpopulations of mosquito hemocytes have been characterized, and immunocytochemical and cytochemical assays have demonstrated that these cells are differentially responsive to invading pathogens (24,27).…”
mentioning
confidence: 99%
“…Several subpopulations of mosquito hemocytes have been characterized, and immunocytochemical and cytochemical assays have demonstrated that these cells are differentially responsive to invading pathogens (24,27). For example, cell types are distinguished by ultrastructural characteristics, phagocytic capacity, or the presence and activity of enzymes involved in the melanin biosynthetic pathway (24,28,29,36). It is hypothesized that hemocytes also participate in pattern recognition and mediate the production of immune peptides from the fat body (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Attempts to increase mosquito resistance to Plasmodium by inducing the overexpression of immune molecules have shown variable success. The induction of NF-kB Rel2 transcription factor (IMD pathway) in midgut and fat body of An.…”
Section: Artículo De Revisiónmentioning
confidence: 99%